Beyond catch-up: VoD interfaces, ITV Hub and the repositioning of television online. (June 2017) - Johnson, Catherine
The past 5 years have seen a rapid acceleration in the development of online television in the United Kingdom and beyond, with rise in ownership of Internet-connected television sets, smartphones and tablets, increased access to broadband and the growing penetration of transaction and subscription video-on-demand (VoD) services. This article asks how free-to-air terrestrial broadcasters are adapting to a media marketplace in which, according to Ofcom, on-demand television is becoming mass market, through an analysis of ITV Hub – the VoD player for the United Kingdom's largest free-to-air advertiser-funded broadcaster. Focusing on the mature UK VoD market and the broadcaster whose business model is most threatened by online television, the article combines trade press and textual analysis to demonstrate how ITV has developed a VoD service highly structured by the logics of broadcasting. Centering its analysis on the interface for ITV Hub, the article argues that this increasingly quotidian form of television ephemera offers a vital site through which to understand the changing nature of television as a medium. The article concludes that with contemporary developments in VoD, the distinctions between linear/broadcast and non-linear/on-demand television (flow vs. file, passive viewer vs. interactive user) are breaking down in ways that challenge prevailing arguments that on-demand television can be understood as offering a distinctly different (and more empowered and interactive) experience for viewers.